ECONOMIC VIOLENCE AGAINST DALIT ENTREPRENEURS IN TAMIL NADU - PARAMASIVAN, Dr.C.; SELVAM, Dr.P. MARI (IJRDO - Journal of Business Management, 2016)
Dalit entrepreneurship is a growing concept which is emerging due to the improvements in socio-economic and educational status of dalit in the country. But dalit in business is not at a significant level while compared to the other communities with this aspect. In the light of this, the present research would be useful to explore the socio economic status, entrepreneurial profile, various problems, violation and discrimination encountered by dalit entrepreneurs in the study area.